Normal histone modifications on the inactive X chromosome in ICF and Rett syndrome cells: implications for methyl-CpG binding proteins - Gartler, Stanley M; Varadarajan, Kartik R; Luo, Ping; Canfield, Theresa K; Traynor, Jeff; Francke, Uta; Hansen, R Scott (BMC biology, 2004)
In mammals, there is evidence suggesting that methyl-CpG binding proteins may play a significant role in histone modification through their association with modification complexes that can deacetylate and/or methylate nucleosomes in the proximity of methylated DNA. We examined this idea for the X chromosome by studying histone modifications on the X chromosome in normal cells and in cells from patients with ICF syndrome (Immune deficiency, Centromeric region instability, and Facial anomalies syndrome). In normal cells the inactive X has characteristic silencing type histone modification patterns and the CpG islands of genes subject to X inactivation are hypermethylated. In ICF cells, however, genes subject to X inactivation are hypomethylated on the inactive X due to mutations in the DNA methyltransferase (DNMT3B) genes. Therefore, if DNA methylation is upstream of histone modification, the histones on the inactive X in ICF cells should not be modified to a silent form. In addition, we determined whether a specific methyl-CpG binding protein, MeCP2, is necessary for the inactive X histone modification pattern by studying Rett syndrome cells which are deficient in MeCP2 function. We show here that the inactive X in ICF cells, which appears to be hypomethylated at all CpG islands, exhibits normal histone modification patterns. In addition, in Rett cells with no functional MeCP2 methyl-CpG binding protein, the inactive X also exhibits normal histone modification patterns. These data suggest that DNA methylation and the associated methyl-DNA binding proteins may not play a critical role in determining histone modification patterns on the mammalian inactive X chromosome at the sites analyzed.